2016
DOI: 10.1186/s12933-016-0419-0
|View full text |Cite
|
Sign up to set email alerts
|

Research into the effect Of SGLT2 inhibition on left ventricular remodelling in patients with heart failure and diabetes mellitus (REFORM) trial rationale and design

Abstract: BackgroundHeart failure (HF) and diabetes (DM) are a lethal combination. The current armamentarium of anti-diabetic agents has been shown to be less efficacious and sometimes even harmful in diabetic patients with concomitant cardiovascular disease, especially HF. Sodium glucose linked co-transporter type 2 (SGLT2) inhibitors are a new class of anti-diabetic agent that has shown potentially beneficial cardiovascular effects such as pre-load and after load reduction through osmotic diuresis, blood pressure redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 56 publications
(60 reference statements)
1
37
0
4
Order By: Relevance
“…31 Other RCTs investigating the effects of SGLT2i on LV remodelling in patients with T2D and HF are currently ongoing. 32,33 A RCT exploring cardiac effects of SGLT2i using impedance cardiography showed that 12 weeks of treatment with dapagliflozin had no significant effects on cardiodynamic parameters related to blood flow (stroke volume, cardiac output, cardiac index), systolic function (ejection fraction, acceleration and velocity indexes, systolic time ratio), circulatory function (systemic vascular resistance index), and fluid status (thoracic fluid content), compared to placebo. 34 Several possible mechanisms have been suggested to explain the beneficial effect of SGLT2i on cardiovascular outcomes, but not yet formally proven.…”
Section: Cardiac Effect and Cardiovascular Outcomesmentioning
confidence: 99%
“…31 Other RCTs investigating the effects of SGLT2i on LV remodelling in patients with T2D and HF are currently ongoing. 32,33 A RCT exploring cardiac effects of SGLT2i using impedance cardiography showed that 12 weeks of treatment with dapagliflozin had no significant effects on cardiodynamic parameters related to blood flow (stroke volume, cardiac output, cardiac index), systolic function (ejection fraction, acceleration and velocity indexes, systolic time ratio), circulatory function (systemic vascular resistance index), and fluid status (thoracic fluid content), compared to placebo. 34 Several possible mechanisms have been suggested to explain the beneficial effect of SGLT2i on cardiovascular outcomes, but not yet formally proven.…”
Section: Cardiac Effect and Cardiovascular Outcomesmentioning
confidence: 99%
“…Further larger studies utilizing novel cardiac imaging modalities to more precisely quantify cardiac structure and function, particularly indicators of early LV dysfunction, would be of great benefit. There are currently ongoing clinical studies that are also utilizing cardiac magnetic resonance imaging to assess the effects of SGLT2 inhibitors on cardiac structure and function, as shown in Table . In addition, studies utilizing speckle‐tracking echocardiography for the measurement of global longitudinal strain and three‐dimensional echocardiography for more accurate quantification of LV structure in people with diabetes and normal LV ejection fraction are underway .…”
Section: The Effect Of Sodium‐glucose Cotransporter 2 Inhibitors On Lmentioning
confidence: 99%
“…Data from an experimental study reported empagliflozin treatment in diabetic and hypertensive rats, resulted in reductions in adverse LV remodelling, as suggested by changes in LV mass, and LV dilatation, while increased cardiac contractility [ 83 ]. The REFORM trial a, phase IV, RCT, aims to shed further by examining the effect of dapagliflozin on LV parameters in patients with known heart failure [ 84 ]. In the meantime, the Dapagliflozin Effect on CardiovascuLAR Events (DECLARE) study is examining the effect of SGLT2 inhibition on CV events in patients without pre-existing macrovascular disease (i.e.…”
Section: Beneficial Effect On Cardiovascular Outcomesmentioning
confidence: 99%